Maximizing Baculovirus-Mediated Foreign Proteins Expression in Mammalian Cells - Yen-Yen Liu, Catherine; Chen, Hong-Zhang; Chao, Yu-Chan (Current Gene Therapy, 2010)
Since the discovery of mammalian cells susceptible to baculovirus transduction in 1995, baculovirus has emerged as a safe, economical and convenient tool for introducing foreign genetic material into mammalian systems. The feasibility of baculovirus as a novel gene transfer vehicle for large scale mammalian protein expression was not obvious at first, as the baculovirus genome is unable to amplify within mammalian cells and expression of the transferred foreign gene does not usually last more than 20 days. However, several recent articles have demonstrated that baculovirus contains both the elements - hr sequences, and the factor - IE2 protein, which can function in mammalian cells to dramatically boost baculovirus-transduced gene expression. The longevity of genes transferred by baculovirus can also be extended by inserting a replication ori with the necessary factors and induce self-replicating episomes. Lastly, peptide-based baculovirus surface modification and two groups of drugs: histone deacetylase inhibitors and microtubule depolymerizing agents, which improve baculovirus gene expression were described. In this article we summarized ways to activate, enhance, and prolong baculovirus-mediated foreign protein expression. The mechanism behind IE2 activation through its unique nuclear body structure was given special emphasis, including our most current data which suggested PML NBs could be disrupted by IE2. Finally, strategies to maximizing mammalian protein production through baculovirus gene transfer are proposed in prospect to current breakthroughs.
Keywords: baculovirus gene therapy